A methodology for estimating the illicit consumption of cigarettes at the country level. Issue 2 (2nd April 2020) - Aziani, Alberto; Dugato, Marco; Meneghini, Cecilia
ABSTRACT: This paper introduces and discusses a methodology for estimating the scale of illicit consumption of cigarettes at a national level. After reviewing current data gathering approaches and estimates, the paper delineates a methodology to estimate the consumption of each type of illicit cigarette (i.e., counterfeits, illicit whites, smuggled/trafficked genuine cigarettes). The proposed methodology is tested through estimating the size and characteristics of the illicit cigarette market in 27 Member States of the European Union in 2016. The results, which underline the heterogeneity in the quality and in the quantity of the illicit consumption of cigarettes in Europe, are presented along with considerations about the strengths and limitations of the proposed methodology in relation to extant approaches.